Germination and initial development of canola and radish submitted to castor leaves aqueous extracts - Rigon, Carlos Alberto Gonsiorkiewicz; Salamoni, Adriana Tourinho; Cutti, Luan; Aguiar, Adalin Cezar Morais de (Comunicata Scientiae, 2016)
This study aimed to evaluate the allelopathic activity of aqueous extracts of castor bean (Ricinus communis L.) leaves on germination and initial growth of canola (Brassica napus L.) and radish (Raphanus sativus L.) seedlings. Two experiments were conducted, usingcanola seeds for the first, which was installed in a 2x7 factorial scheme (with two photoperiods – dark and light and seven extracts concentrations - 0, 1, 2, 4, 8, 16 and 32%). The second experiment consisted of an evaluation of radish seed germination submitted to seven concentrations of the extracts in the dark photoperiod. The germination of the canola seeds was reduced in the dark, and the use of extracts at concentrations of 16% and 32%inhibited seeds germination for both studied photoperiods. The radish seed germination was completely inhibited when the concentration of 32% was used, however, at the concentrations of 4, 8 and 16% a reduction on rootand hypocoyl development of the seedlings were observed, affirming the high allelopathic potential of castor bean aqueous extracts on canola and radish.